Ochrona danych biometrycznych pracownika - Giedrewicz-Niewińska, Aneta (PRAWO i WIĘŹ, 2025)
Biometric techniques can be used in the workplace to protect the interests of both employers and employees. They can help to adapt working conditions to employees' needs. Conversely, employers can use the processing of biometric data to implement workplace controls, particularly with regard to access to important information or sensitive areas. However, using biometric techniques can involve significant interference with privacy and other personal rights, posing a threat to the dignity of those concerned. This study aims to identify the privacy risks associated with processing employee biometric data. The discussion will focus on understanding what biometric data are and the current legal regulations on processing biometric data in an employment context.